2021
DOI: 10.1111/obr.13216
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on immune response to infection: Plausible mechanisms and outcomes

Abstract: Summary Emerging data suggest an association between obesity and infectious diseases. Although the mechanisms underlying this link are not well established, a number of potential factors may be involved. Indeed, the obesity‐related vulnerability to infectious diseases could be due to chronic low‐grade inflammation, hyperglycemia, hyperinsulinemia, and hyperleptinemia, which lead to a weakening of both the innate and adaptive immune responses. In addition, obesity results in anatomical–functional changes by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 98 publications
0
38
1
Order By: Relevance
“…Obesity is associated with chronic low-grade inflammation ( 27 ), high leptin and C-reactive protein (CRP) ( 28 ), and altered immune responses ( 29 ). Indeed, dysregulated immune responses to various pathogens is well-documented in obese individuals, including an exacerbated TNF-α and IL-6 response that is accompanied by suppressed T-cell responses to bacterial and viral infections ( 30 , 31 ). Obesity is associated with reduced immune response to influenza infection and vaccination ( 32 ) as well as disruptions of lymphoid tissue integrity in addition to alterations in leukocyte development, phenotypes and functions ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with chronic low-grade inflammation ( 27 ), high leptin and C-reactive protein (CRP) ( 28 ), and altered immune responses ( 29 ). Indeed, dysregulated immune responses to various pathogens is well-documented in obese individuals, including an exacerbated TNF-α and IL-6 response that is accompanied by suppressed T-cell responses to bacterial and viral infections ( 30 , 31 ). Obesity is associated with reduced immune response to influenza infection and vaccination ( 32 ) as well as disruptions of lymphoid tissue integrity in addition to alterations in leukocyte development, phenotypes and functions ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that hospitalized PLWO were younger than those without obesity. Although younger individuals have less risk of infections and complications than older people due to having fewer comorbidities and a stronger immune system, this is not the case for those with obesity [ 2 , 7 , 30 32 ]. Some authors have postulated that PLWO younger than 60 years could have a greater risk of severe COVID-19 outcomes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of this condition on the development of bacteremia caused by C. haemolyticum remains unclear. However, it cannot be ruled out considering the fact that obesity may cause various alterations of the immune system [ 25 ].…”
Section: Discussionmentioning
confidence: 99%